(untitled) (Proceedings of International Educators Conference, 2022)
This article toponomic data main study object Kashkadarya province Dehkanabad of the district Beshkotan of the village come exit history in detail stopping passed. Dehkanabad district east of their peoples economic, cultural, commercial and your friendship important bond being service by doing the arrival in the article separately emphasizing passed. This in the article our statehood history Kashkadarya oasis cities importance in learning Boston village in the example studied.